Physiological and performance responses to intermittent uchi-komi in judo - Franchini, E.; Panissa, V. L. G.; Julio, U. F. (The Journal of Strength and Conditioning Research, 2013)
The objective of this study was to compare the physiological and performance responses with different judo techniques and time structure uchi-komi (technique entrance) protocols. Ten judo athletes (25 ± 6 years old, 73 ± 9 kg, 173 ± 5 cm, and 15 ± 6 years of judo experience) were submitted to 9 all-out uchi-komi sessions. Three techniques (o-uchi-gari, seoi-nage, and harai-goshi) and 3 different time structures (18 × 10 seconds/10 seconds, 9 × 20 seconds/20 seconds, and 6 × 30 seconds/30 seconds) were randomly assigned. Two-way and 3-way analyses of variance with repeated measurements and the Bonferroni test were used. The significance level was fixed at 5%. There was no effect of the time structure or the technique on the absolute energy expenditure (p > 0.05), which can be attributed to the all-out characteristic of the exercise. However, more repetitions were executed during the o-uchi-gari protocol (F = 19; p < 0.001; ?2 = 0.32) compared with harai-goshi and seoi-nage (p < 0.001 for both comparisons). Oxygen consumption differed over time during the activity (F = 767; p < 0.001; ?2 = 0.904), with lower values during the first minute (32.51 ± 3.21 ml/kg/min) compared with the second (41.47 ± 4.20 ml/kg/min) and third minutes (42.96 ± 4.29 ml/kg/min), and lower values were recorded in the second minute compared with the third minute (p < 0.001 for all comparisons). There was also an effect of technique on the total energy expenditure per repetition (F = 6; p = 0.001; ?2 = 0.128), with o-uchi-gari resulting in lower values compared to seoi-nage (p = 0.003), as the former technique does not involve torso rotation and knee flexion, while the latter technique does. These training protocols resulted in similar oxygen uptake and heart rate responses compared to match simulations, and they can be used to simulate the match demand.